Biochar and anionic polyacrylamide modulated soil hydraulic functions catalyze water saving, root development and yield of basmati rice - Sharma, Peeyush; Abrol, Vikas; Shabir, Haziq; Gupta, S. K.; Gupta, N. K.; Samnotra, R. K.; Chandra, Subhash; Bashir, Owais; Amjid, Sheikh; Singh, Priti; Hashem, Abeer; Kumar, Ajay; et al. (Frontiers in Plant Science, 2025)
IntroductionEfficient water use while maintaining rice productivity remains a major challenge amid declining water resources. Biochar with large surface area and hydrophilic polymers, such as anionic polyacrylamide (PAM), can enhance soil moisture and nutrient retention. However, their combined effects on rice growth and soil hydro-physical properties have not been fully explored.MethodsThis study evaluated the influence of biochar and PAM on soil properties, water retention, root growth, and rice performance under two establishment methods: the System of Rice Intensification (SRI) and Conventional Method (CM). A two-year field experiment was conducted on sandy clay loam soil using a split-plot design with SRI and CM as main plots and six soil amendment treatments (control, biochar, and polymer) as subplots, replicated thrice.Results and discussionResults showed that SRI produced 15% higher grain yield while using 28.2% less irrigation water compared with CM. SRI also improved soil moisture (SM) content, infiltration rate (IR), hydraulic conductivity (HC), and water productivity (WP) by 6.6%, 64 5.4%, 9.0%, and 46.5%, respectively. Root length and weight densities under SRI were 1.31 and 1.62 times higher than under CM. The application of biochar (10 t ha⁻¹) and PAM (10 kg 66 ha⁻¹) significantly enhanced soil physical attributes, resulting in 1.22 and 1.27 times increases in grain yield and root length density, respectively, over the control. Integrating biochar and polymer with SRI reduced irrigation water use by 39.45% compared with CM. Overall, the combination of biochar (10 t ha⁻¹) and PAM (10 kg ha⁻¹) under SRI effectively improved soil hydro-physical properties, root development, water productivity, and rice yield in the sub-humid tropical Inceptisols of northern India.